A novel infrastructure for the continuous monitoring of soil CO2 emissions: a case study at the alto Tiberina near fault observatory in Italy - Caracausi, Antonio; Camarda, Marco; Chiaraluce, Lauro; De Gregorio, Sofia; Favara, Rocco; Pisciotta, Antonino (Frontiers in Earth Science, 2023)
Static and dynamic stress trigger, along with earthquakes, the emission and migration of crustal fluids, as frequently observed on the surface and within the upper crust of tectonically active areas, such as the northern Apennines of Italy. To investigate the origin of these fluids and their interconnection with the seismogenic process, we complemented The Alto Tiberina Near Fault Observatory (TABOO-NFO), a multidisciplinary monitoring infrastructure composed of a dense array of seismic, geodetic, strain, and radon sensors, with a proper geochemical network grounded on four soil CO2 flux monitoring stations and weather sensors, placed near the main vents of the superficial manifestations. The TABOO-NFO is a state-of-the-art monitoring infrastructure, which allows in studying various geophysical parameters connected to the deformation processes active along a crustal fault system dominated by the Alto Tiberina fault (ATF), which is a 60 km long normal fault dipping at a low angle (<15°-20°). The region is favourable for conducting geochemical studies, as it is characterised by the presence of over pressurised fluids trapped at certain depths and superficial manifestations associated with the emission of large quantities of fluids. After describing the theoretical framework and the technological aspects based on which we developed the geochemical monitoring network, we described the data recorded in the first months. Over the studied period, the results showed that soil CO2 flux was primarily influenced by environmental parameters, and that the selected sites received a regular supply of deep-origin CO2